Plasticidade fenotípica em espécies de peixes ornamentais: relacionando ecologia, fisiologia e epigenética - Caldas, Waldir Heinrichs (Genética, Conservação e Biologia Evolutiva - GCBEv, 2021)
Fishes’ responses to hypoxia seem to be related to the diversity of aquatic environments, which present daily and seasonal variations in the dissolved oxygen concentration. Amongst these fishes’ adaptation to hypoxia, behavioral, metabolic, physiological, and biochemical responses are well known for some species. Many of these responses are controlled by genetic and possibly epigenetic mechanisms, such as microRNAs (miRNAs). MiRNAs are epigenetic mechanisms that act at the interface of the environment and the transcriptome and are known to drive plasticity in the responses following environmental stressors. An area of miRNA that has remained underexplored is the function of miRNAs in hypoxia tolerance, its sex specific action following hypoxia exposure and its effects as gene expression regulator in fishes. In this work, we aimed to identify how two different aquatic environments, normoxic forest streams and hypoxic lakes, dictate the responses to hypoxia for two cichlid species, Mesonauta festivus and Aequidens pallidus. In the first chapter, the results show that A. pallidus is less tolerant to hypoxia, which seems to be related to this animal’s natural normoxic environment. Even though this species modulates the mitochondrial respiration in order to improve the oxygen use, it also shows a lower decrease in metabolic rate when exposed to hypoxia, and no activation of the anaerobic metabolism. Instead, M. festivus showed a higher decrease in metabolic rate and an activation of the anaerobic metabolism after hypoxia exposure. These data reveal that the natural dissolved oxygen influences the hypoxia tolerance and that species’ tolerance is related to its ability to perform metabolic depression. The interesting results are the absence of mitochondrial respiration influence in these processes. Following the hypoxia tolerance found for both these species, in the second chapter, this work aimed to evaluated the expression of miR-210, miR-181c, miR-18a, miR-21, and let-7d in these two Amazon species, which have distinct hypoxia tolerance strategies. The results show that, when exposed to hypoxia, M. festivus changes the expression of miR-181c and let-7d in the liver, while A. pallidus changes the expression of miR-181c and miR-210 in the liver. The results also confirm that the changes in expression of these miRNAs are related to these fishes’ strategy to endure hypoxia. The third chapter in this study aimed to identify differences in mRNA and miRNA expression in the F1 generation of zebrafish (Danio rerio) at 1 hpf after either F0 parental male and female exposed to 2 weeks of continuous (45%) hypoxia. In general, F1 embryos at 1 hpf demonstrated differences in mRNA and miRNAs expression related to the stressor and to the specific sex of the F0 that was exposed to hypoxia. Bioinformatic pathway analysis of predicted miRNA:mRNA relationships indicated responses in known hypoxia signaling and mitochondrial bioenergetic pathways. This research demonstrates the importance of examining the specific male and female contributions to phenotypic variation in subsequent generations and provides evidence that there is both maternal and paternal contribution of miRNA through eggs and sperm from one generation to the next when the first is exposed to hypoxia.
Keywords: Hipóxia; Epigenética